Digital Accessibility in Libya: Reality and Aspirations - Salim Aloud; Ali Wadi; Abdulmunem Almuktar (AlQalam Journal of Medical and Applied Sciences, 2026)
The term "digital accessibility" is relatively new in Libya, as the Libyan state has yet to develop its own policies and legislation regarding digital accessibility. Furthermore, most people in Libya, whether officials or ordinary citizens, still lack a clear definition of digital accessibility. The term "digital accessibility" refers to enabling all individuals, including people with disabilities, to access and utilize digital services and platforms on an equal basis with others. This study aims to raise awareness about policies and initiatives related to digital accessibility, provide an overview of the current state of digital accessibility in Libya, compare it with regional and global contexts, and offer recommendations for steps to be taken to advance this area.